Comparison of leptin and estrone levels between normal body mass index and obese menopausal women - Siregar, Muhammad FG.; Terauchi, Masakazu; Sari, Rizka A.; Adella, Cut A.; Prabudi, Muhammad O.; Barus, Melvin NG.; Rivany, Riza; Tobing, Immanuel DL.; Azmeila, Selly (Narra Sains Indonesia, 2024)
Postmenopausal women often experience hormonal changes and shifts in fat composition, affecting weight gain and obesity. Understanding the link between hormones, especially estrogen and leptin, is key to managing weight and lowering disease risk in menopausal women. The aim of this study was to compare the levels of leptin and estrone in menopausal women with normal weight and obesity. A cross-sectional study was conducted on menopausal women, either normal body mass index (BMI) or obese, at H. Adam Malik General Hospital, Medan, Indonesia. Blood samples were collected to measure leptin and estrone levels using the enzyme-linked immunosorbent assay (ELISA) method. The differences in leptin levels between groups were analyzed using the Wilcoxon test, while the correlation between BMI and leptin was examined using the Pearson correlation test. The disparity in estrone levels in both groups was analyzed using the Mann-Whitney test and the correlations between variables were assessed using the Spearman or Pearson correlation tests as appropriate. The mean leptin levels in normal BMI and obesity groups were 17.73±4.96 and 25.46±12.95 ng/mL, respectively, and were statistically different (p=0.006). The mean estrone levels in menopausal women with normal BMI and obesity were 943.23±391.79 and 851.38±282.23 ng/mol, respectively and were not statistically different (p=0.564). A significant positive correlation was found between BMI and leptin level (r=0.59; p<0.001), while BMI and estrone were not significantly correlated (r=0.083; p=0.559). In conclusion, leptin level was significantly different between BMI groups and had a strong positive correlation with BMI. This finding could be an important insight in body weight management and disease risk prevention in menopausal women.